Bulk vs. surface flame retardancy of fully bio-based polyamide 10, 101. Issue 49 (30th May 2015) - Battegazzore, Daniele; Alongi, Jenny; Fontaine, Gaelle; Frache, Alberto; Bourbigot, Serge; Malucelli, Giulio
<x xml:space="preserve">Abstract</x> PA 10, 10 can be flame retarded either by melt-blending the polymer with intumescent formulations or by coating it with UV-curable mixtures.